Reliable Digit Span: Does it Adequately Measure Suboptimal Effort in an Adult Epilepsy Population?. (5th April 2018) - Maiman, Moshe; Del Bene, Victor A; MacAllister, William S; Sheldon, Sloane; Farrell, Eileen; Arce Rentería, Miguel; Slugh, Mitchell; Nadkarni, Siddhartha S; Barr, William B
Abstract: Objective: Assessment of performance validity is a necessary component of any neuropsychological evaluation. Prior research has shown that cutoff scores of ≤6 or ≤7 on Reliable Digit Span (RDS) can detect suboptimal effort across numerous adult clinical populations; however, these scores have not been validated for that purpose in an adult epilepsy population. This investigation aims to determine whether these previously established RDS cutoff scores could detect suboptimal effort in adults with epilepsy. Method: Sixty-three clinically referred adults with a diagnosis of epilepsy or suspected seizures were administered the Digit Span subtest of the Wechsler Adult Intelligence Scale (WAIS-III or WAIS-IV). Most participants (98%) passed Trial 2 of the Test of Memory Malingering (TOMM), achieving a score of ≥45. Results: Previously established cutoff scores of ≤6 and ≤7 on RDS yielded a specificity rate of 85% and 77% respectively. Findings also revealed that RDS scores were positively related to attention and intellectual functioning. Given the less than ideal specificity rate associated with each of these cutoff scores, together with their strong association to cognitive factors, secondary analyses were conducted to identify more optimal cutoff scores. Preliminary results suggest that an RDS cutoff score of ≤4 may be more appropriate in a clinically referred adult epilepsy population with a low average IQ or lower. Conclusions: Preliminary findings indicate that cutoff scores of ≤6 and ≤7 on RDS are not appropriate in adults with epilepsy, especially in individuals with low average IQ or below.